(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the organization of physical education and sports activities in private educational institutions through the application of innovative methods, using gymnastics lessons as an example. The study analyzes the positive impact of modern technologies and interactive approaches on the educational process, student engagement, and physical development. It also describes the necessary conditions and pedagogical approaches for the effective implementation of innovative methods. The article concludes with practical recommendations for private schools and outlines promising directions for future research.